2014
DOI: 10.4049/jimmunol.1302281
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell–Evasive Functions of Human Cytomegalovirus Display Pervasive MHC Allele Specificity, Complementarity, and Cooperativity

Abstract: Immunoevasive proteins (“evasins”) of human CMV (HCMV) modulate stability and localization of MHC class I (MHC I) molecules, and their supply of antigenic peptides. However, it is largely unknown to what extent these evasins interfere with recognition by virus-specific CD8 T cells. We analyzed the recognition of HCMV-infected cells by a panel of CD8 T cells restricted through one of nine different MHC I allotypes. We employed a set of HCMV mutants deleted for three or all four of the MHC I modulatory genes US2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…To circumvent this problem, we chose an HCMV strain that lacked several of the MHC immunoevasins. Such strains modulate antigen presentation to a lesser extent than HCMV isolates expressing the full complement of immunoevasins [73, 74]. In view of these considerations, we value the comparable activation and proliferation of HCMV-specific T cells observed upon co-cultivation with ULBP2-TB40 and TB40 infected DCs (Figs 3 and 4C) as a positive result.…”
Section: Discussionmentioning
confidence: 86%
“…To circumvent this problem, we chose an HCMV strain that lacked several of the MHC immunoevasins. Such strains modulate antigen presentation to a lesser extent than HCMV isolates expressing the full complement of immunoevasins [73, 74]. In view of these considerations, we value the comparable activation and proliferation of HCMV-specific T cells observed upon co-cultivation with ULBP2-TB40 and TB40 infected DCs (Figs 3 and 4C) as a positive result.…”
Section: Discussionmentioning
confidence: 86%
“…32–34 More recent studies also indicate that presentation of CMVpp65 peptides, which does not require new protein synthesis, may be less susceptible to inhibition by subsequently generated evasins, the non-coding RNAs generated by CMV that can interfere with antigen processing and TAP mediated transport of antigen peptides to HLA alleles for presentation. 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…For example, evasins such as US2,3,6 and 11 can disrupt the membrane localization and stability of specific MHC class I alleles, thereby impairing their expression. 35,49,50 US3 and US6 can also prevent the transport and loading of processed peptides on HLA class I alleles for presentation to T-cells. 36 In addition, Kim et al 51 have recently shown that a CMV micro RNA US4-1 can downregulate the expression of an aminopeptidase essential to the editing of antigenic peptides during their processing within the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…We want to point out that both mutants also lacked ORFs US2 to US6 encoding immune evasins and were therefore expected to modulate HLA expression to a lesser extent than wildtype CMV (61). This characteristic of the mutants appeared to be a prerequisite for measuring the influence of UL11 on T cell activity, because many CMV-specific T cells are hardly activated when HLA levels are diminished (62,63). Immunoblot analysis of cells infected with the two mutants confirmed the similar expression of the IE1 and pp65 proteins (Fig.…”
Section: Expression Of Ul11 Proteins During the Lytic CMV Infection Cmentioning
confidence: 99%